2014
DOI: 10.1080/01650521.2014.972187
|View full text |Cite
|
Sign up to set email alerts
|

Pollinator sharing and low pollen–ovule ratio diminish reproductive success in two sympatric species ofPortulaca(Portulacaceae)

Abstract: We studied the breeding systems, phenology, pollination, and reproductive success of Portulaca grandiflora and P. hirsutissima (Portulacaceae) at Parque Nacional do Catimbau in the Brazilian Caatinga. The species flowered synchronously, exhibited similar floral morphology, offered pollen as the sole floral resource and shared the same bee species as pollinators. They visited flowers of both Portulaca species at similar frequencies, and their visitation peaks occurred at the same time of day. The pollinators ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
2
1
Order By: Relevance
“…In this study, a short period of opening flower was observed for the two populations of T. fruticosum evaluated. Nevertheless, short periods of opening flower were also observed for other species of this botany family (Pinto & Schlindwein 2015), although in the current study levels of pollen viability were much lower than the study cited above.…”
contrasting
confidence: 65%
“…In this study, a short period of opening flower was observed for the two populations of T. fruticosum evaluated. Nevertheless, short periods of opening flower were also observed for other species of this botany family (Pinto & Schlindwein 2015), although in the current study levels of pollen viability were much lower than the study cited above.…”
contrasting
confidence: 65%
“…Our results indicate the occurrence of pollinator limitation on fruit set in the Rio Preto population but not in Diamantina, whereas the Diamantina but not the Rio Preto population seems to be resource limited. Low visitation frequency, variation in pollination efficiency, and pollinators sharing has been identified as possible causes of pollinator limitation (Ashman et al, 2004;Hegland and Totland, 2007;Pinto and Schlindwein, 2015). In the Rio Preto Park (and not in Diamantina), C. minensis occurs with further two columnar cacti, Pilosocereus aurisetus (Werderm.)…”
Section: Discussionmentioning
confidence: 99%
“…Many Opuntia species overlap in flowering (synchronopatric species) and share the main pollinators, which leads to competition for floral visitors (Grant et al ; Grant & Grant ; Osborn et al ; Schlindwein & Wittmann ), causing interspecific pollen flow, reduced reproductive success, natural hybrid formation or even the exclusion of species (Waser ; Grant & Grant ; Osborn et al ; Schlindwein & Wittmann ; Morales & Traveset ; Pinto & Schlindwein ). In some cases, however, synchronous flowering can attract higher richness and abundance of floral visitors and pollinators, leading to increased reproductive success (Ghazoul ).…”
Section: Introductionmentioning
confidence: 99%